A large solitary fibroma of the deep compartment of the sole. (June 2017) - Lui, T.H.
Highlights: Fibroma usually presents as nodules of the plantar aponeurosis. Fibroma occasionally presents as a mass deep and away from the aponeurosis. Resection of deep plantar fibroma is risky to the neurocascular structures. Fibroma of the deep compartment of the sole can be resected en-bloc through a dorsal approach by dislocation of the tarsometatarsal joints. Abstract: A 50-year-old lady presented with a right foot mass and pain for 1 year. Magnetic resonance imaging showed a 3.9 × 3.2 × 5 cm mass on plantar side of the forefoot deep to the major flexor tendons and plantar aponeurosis and inferior to 1st–4th metatarsals. The mass extended dorsally through the intermetatarsal space to the foot dorsum. Ultrasound guided biopsy was performed, which confirmed it was a fibroma. This case was further complicated by pathological fracture of the 3rd metatarsal. It was resected through a dorsal incision and surgical dislocation of the 2nd and 3rd tarsometatarsal joints. Magnetic resonance imaging was repeated 1 year later and showed complete resection of the lesion without recurrence.